Business Development Foundations: Researching Market and Customer Needs. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2018)
Learn business development concepts to better understand your market and clients. Discover how to speak like a leader, unpack your competitors' strengths and weaknesses, and more.